Blood mitochondrial enzymatic assay as a predictor of long-term outcome in severe traumatic brain injury. (August 2016) - Sinha, Sumit; Raheja, Amol; Samson, Neha; Bhoi, Sanjeev; Selvi, Arul; Sharma, Pushpa; Sharma, Bhawani Shankar
Highlights: This is the first clinical trial associating enzymatic mitochondrial assay to global neurological outcome. Blood mitochondrial assay reflects global reduction–oxidation (redox) status. Higher admission and day 7 Complex I activity was associated with favorable outcome at 1 year. Delayed elevation of Complex IV activity reflects chronic oxidative stress. Higher admission pyruvate dehydrogenase complex activity was associated with unfavorable outcome at 1 year. Abstract: Recent studies have observed the central role of mitochondrial dysfunction in severe traumatic brain injury (sTBI). One hundred and seven sTBI patients (18–65 years old, presenting within 8 hours of injury) were randomised for a placebo controlled phase II trial of progesterone with or without hypothermia. We serially analysed blood mitochondrial enzymes (Complex I [C1], Complex IV [C4] and pyruvate dehydrogenase complex [PDH]) using a dipstick assay at admission and 7 days later for 37 patients, irrespective of assigned group. Favorable Glasgow Outcome Scale (GOS) at 1 year was associated with admission C1 levels above 0.19 μg, admission C4 levels above 0.19 μg and day 7 C1 levels above 0.17 μg, all per 25 μl of blood. Unfavorable GOS at 1 year was associated with admission serum PDH levels above 0.23 μg/25 μl of blood. Survivors at 1 year had significantly higher admission serum C1 levels above 0.19 μg/25 μl and day 7 C1 levels above 0.17 μg/25 μl. To our knowledge this is the first clinical trial associating blood mitochondrial enzymes with long-term outcome in sTBI. Serial monitoring and optimisation of blood C1, C4 and PDH levels could aid in prognostication and potentially guide in using mitochondrial targeted therapies. Blood mitochondrial enzymatic assay might suggest global reduction–oxidation status.